SEDIMENTATION AND FACIES ANALYSIS OF VOLCANICLASTICUNIT WITHIN MAQDADIA FORMATION,INJANA AREA,SOUTHERN HEMRIN, NE IRAQ - Al-Hassan, Muhammad; AL-Zaidy, Ali (Iraqi Journal of Science, 2024)
Field observations revealed the occurrence of volcaniclstic units (pyroclasticunits) within the Muqdadyia Formation (Pliocene) in Injana area, southern Hemrinanticline; these rock-units located along Tayawi, Magrin and Zarloukh sections andhas been called as a volcaniclastic unit of Muqdadyia Formation.the facies analysis for the volcaniclastic units is part of succession which wasdeposited in a fluvio-laucustrine environment. This succession is divided into eightfacies on the basis of deposition and transportion settings into:- 1-Primary tuff rock(non-reworking), this represent the surge facies (A1) and fallout facies (A2) whichdeposited in a quiet environment (lake or marsh) near Zarloukh area; 2-Secondarytuff rock these represent the sandy tuffstone (B1), mudy tuffstone (B2) and clayeytuffstone (B3) which deposited in meander active channel environment during highconcentration supply. And tuffaceous sand (C1), tuffaceous mudstone (C2) andtuffaceous claystone (C3) which were deposited in the same environment but duringlow concentration volcaniclasts supply. Accordingly, the rock unit deposited by twostages of the supplying in volcaniclasts during three deposition cycles.